Herb Hydraulics: Inter- and Intraspecific Variation in Three Ranunculus Species. Issue 4 (19th February 2016) - Nolf, Markus; Rosani, Andrea; Ganthaler, Andrea; Beikircher, Barbara; Mayr, Stefan
Abstract : Small herbaceous species are vulnerable to water stress but adjusted to their habitat conditions and internally coordinated to avoid hydraulic failure. Abstract: The requirements of the water transport system of small herbaceous species differ considerably from those of woody species. Despite their ecological importance for many biomes, knowledge regarding herb hydraulics remains very limited. We compared key hydraulic features (vulnerability to drought-induced hydraulic decline, pressure-volume relations, onset of cellular damage, in situ variation of water potential, and stomatal conductance) of three Ranunculus species differing in their soil humidity preferences and ecological amplitude. All species were very vulnerable to water stress (50% reduction in whole-leaf hydraulic conductance [ k leaf ] at −0.2 to −0.8 MPa). In species with narrow ecological amplitude, the drought-exposed Ranunculus bulbosus was less vulnerable to desiccation (analyzed via loss of k leaf and turgor loss point) than the humid-habitat Ranunculus lanuginosus . Accordingly, water stress-exposed plants from the broad-amplitude Ranunculus acris revealed tendencies toward lower vulnerability to water stress (e.g. osmotic potential at full turgor, cell damage, and stomatal closure) than conspecific plants from the humid site. We show that small herbs can adjust to their habitat conditions on interspecific and intraspecific levels in various hydraulic parameters. The coordination of hydraulic thresholds (50% and 88% loss of k leaf, turgor loss point, and minimum in situ water potential) enabled the study species to avoid hydraulic failure and damage to living cells. Reversible recovery of hydraulic conductance, desiccation-tolerant seeds, or rhizomes may allow them to prioritize toward a more efficient but vulnerable water transport system while avoiding the severe effects that water stress poses on woody species.